Cervical artery dissection after upper respiratory infection: clinical features and prognosis - Sara D. B. Rosa; Mafalda Soares; Ana Paiva Nunes; Liqi Shu; Eileen Wu; Nils Henninger; Jayachandra Muppa; Mirjam R. Heldner; Kateryna Antonenko; Setareh Omran; Ahmad Nehme; Aaron Rothstein; et al. (Acta Neurologica Belgica, 2026)

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

Management of tree density to sustain Kirtland’s warbler breeding habitat and timber production from jack pine plantations - Megan Machusko; David E. Rothstein; Amy D. Bleisch (Forest Ecology and Management, 2024)

A novel founder MSH2 deletion in Ethiopian Jews is mainly associated with early-onset colorectal cancer - I. Kedar; L. Walsh; G. Reznick Levi; S. Lieberman; A. Abu Shtaya; S. Naftaly Nathan; I. Lagovsky; R. Tomashov-Matar; M. Goldenberg; L. Basel-Salmon; L. Katz; O. Aleme; et al. (Familial Cancer, 2022)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Knockout of MCT1 results in total absence of spermatozoa, sex hormones dysregulation, and morphological alterations in the testicular tissue - Raquel L. Bernardino; Warren N. D’Souza; Luis Rato; Jay L. Rothstein; Tânia R. Dias; Daniel Chui; Sharon Wannberg; Marco G. Alves; Pedro F. Oliveira (Cell and Tissue Research, 2019)

Food purchase patterns indicative of household food access insecurity, children’s dietary diversity and intake, and nutritional status using a newly developed and validated tool in the Peruvian Amazon - Ramya Ambikapathi; Jessica D. Rothstein; Pablo Peñataro Yori; Maribel Paredes Olortegui; Gwenyth Lee; Margaret N. Kosek; Laura E. Caulfield (Food Security, 2018)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Jack pine foliar δ15N indicates shifts in plant nitrogen acquisition after severe wildfire and through forest stand development - Stephen D. LeDuc; David E. Rothstein; Zhanna Yermakov; Susan E. Spaulding (Plant and Soil, 2013)

Ectomycorrhizal fungal succession coincides with shifts in organic nitrogen availability and canopy closure in post-wildfire jack pine forests - Stephen D. LeDuc; Erik A. Lilleskov; Thomas R. Horton; David E. Rothstein (Oecologia, 2013)

Genome-scan for IQ discrepancy in autism: evidence for loci on chromosomes 10 and 16 - Nicola H. Chapman; Annette Estes; Jeff Munson; Raphael Bernier; Sara J. Webb; Joseph H. Rothstein; Nancy J. Minshew; Geraldine Dawson; Gerard D. Schellenberg; Ellen M. Wijsman (Human Genetics, 2011)

Linkage and association analyses identify a candidate region for apoB level on chromosome 4q32.3 in FCHL families - Ellen M. Wijsman; Joseph H. Rothstein; Robert P. Igo; John D. Brunzell; Arno G. Motulsky; Gail P. Jarvik (Human Genetics, 2010)

Plant‐available organic and mineral nitrogen shift in dominance with forest stand age - Stephen D. LeDuc; David E. Rothstein (Ecology, 2010)
Studies of soil nitrogen (N) availability over stand development have almost exclusively focused on mineral N, yet we increasingly recognize that plants can take up organic N in the form of free amino acids at biologically important rates. We investigated amino‐acid and mineral N availability along a 10‐site chronosequence of jack pine stands, varying in age from 4 to 60 yr following wildfire. We measured free amino‐acid N and mineral N in soil extracts; native proteolytic rates; net N mineralization rates; and microbial amino‐acid consumption via a 15 N leucine tracer assay in 6 of the 10 sites (4, 10, 18, 22, 46, and 55‐yr‐old). Amino‐acid N was consistently low in the youngest sites (4–10 yr), increased rapidly in mid‐aged sites (15–22 yr), and was highest in stand age 46. In contrast, mineral N exhibited a parabolic shape ( R 2 = 0.499; P P = 0.632). Percentage 15 N tracer recovery was lowest in the extractable organic N pool for the 4, 10, and 18‐yr‐old sites, though only site age 10 was significantly different from the older sites. Percentage of recovery in the organic N pool was significantly positively related ( R 2 = 0.798; P

Aquaporin 4 is increased in association with human immunodeficiency virus dementia: Implications for disease pathogenesis - Coryse St Hillaire; Diana Vargas; Carlos A Pardo; Dan Gincel; Jacquelyn Mann; Jeffrey D Rothstein; Justin C McArthur; Katherine Conant (Journal of NeuroVirology, 2005)

Olfactory neuron-specific expression of NeuroD in mouse and human nasal mucosa - Ken-ichi Nibu; Guoqi Li; Xunling Zhang; Nancy E. Rawson; Diego Restrepo; Kimitaka Kaga; Louis D. Lowry; William M. Keane; Jay L. Rothstein (Cell and Tissue Research, 1999)

The basis for female choice in an avian brood parasite - D. A. Yokel; S. I. Rothstein (Behavioral Ecology and Sociobiology, 1991)